Audit Committee Financial Expertise and Financial Reporting Timeliness - Ehigie, Aimienrovbiye Humphrey; Isenmilia, P. A. (Richtmann Publishing, 2022)
This study examines conceptually the relevance of the audit committee financial expertise to financial reporting timeliness of a firm. The methodology adopted in this study is library research whereby relevant and extant literature related to the audit committee financial expertise and financial reporting timeliness. Audit committee financial expertise was x-ray from the perspective of accounting financial expertise and the non-accounting financial expertise. Observations from the study highlights that the presence of accounting financial experts in an audit committee is an important element that mitigate reportorial challenges and motivates financial reporting timeliness. The study recommends that financial experts in the audit committee should be given more power to enable them discharge their duty effectively and efficiently, the definition of audit committee financial expertise should not relegate other relevant profession to the background, and the impact of the audit committee financial expertise on audit expectation gap should be considered when appointing members of the audit committee. Received: 3 February 2022 / Accepted: 23 February 2022 / Published: 5 March 2022